Design and Development of a Web-Based SBMPTN Try-Out Application: A Case Study at SMK N 2 Kotabumi - Maryana; Ryan Aji Wijaya (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
This research is motivated by the suboptimal state of exam simulation media for students at SMK N 2 Kotabumi in preparing for the Joint Entrance Examination for State Universities (SBMPTN), where conventional tryout processes result in slow and inaccurate data processing. As a solution to these issues, this study designs a web-based tryout application developed using the Waterfall method through the stages of requirement analysis, design, coding, and systematic testing. The application is designed to simulate the Computer Assisted Test (CAT) mechanism in real-time, thereby providing instant and transparent assessment feedback for both students and the school. The results of this research are expected to provide an effective self-simulation platform to enhance academic readiness and the accountability of student learning evaluations at SMK N 2 Kotabumi, ultimately achieving a more competitive graduation quality at the national level.